representación lgbtiq+ a través y mediante el arte. - Zarate Alban, Genesis Angelina (Machala: Universidad Tecnica de Machala, 2024)
This degree project called "LGBTIQ+ Representation through art" aims to create a series of surrealist portraits that represent and give visibility to people of the community in Ecuador. This work seeks to inform and raise awareness about the problems of discrimination still faced by this minority group. Discrimination and invisibility are persistent problems for the LGBTIQ+ community in Ecuador, and this project aims to address these challenges through the powerful tool of art. The choice of surrealism as an artistic movement is due to its characteristic method of expression, which explores the subconscious based on Freud's theories. This approach allows for the creation of more creative and unconventional works. Surrealism, with its ability to depict the irrational and dreamlike, provides a suitable framework to reflect the complexities and unique experiences of LGBTIQ+ people. By utilizing this style, one can go beyond literal representation and delve into the depths of the subconscious, where many of the internal struggles and hidden aspects of these people's identities are found. Through a series of interviews with 5 individuals related to the subject matter of the project, we plan to create a series of portraits that tell the story of the LGBTIQ+ community from its beginnings to the present day. These interviews are fundamental to capture the personal experiences and the stories of struggle and resistance of each individual, the aim is not only to document their experiences, but also to interpret and translate these stories into visual elements that make up the portraits. The works in question will be exhibited on social networks such as Instagram and Facebook, with the aim of generating a space for debate on how art has the power to change perceptions and build bridges between different parts of society. Social networks are chosen as an exhibition platform because of their ability to reach a wide audience and encourage interaction. By sharing these works online, the hope is to not only make the stories of LGBTIQ+ people visible, but also to provoke reflections and conversations about equality and social justice. This project is an example of how art can be used to advocate for equality and social justice. Through the creation of these surreal portraits, it seeks to not only represent LGBTIQ+ people, but also to honor their stories and struggles. By giving them a space in art, we contribute to the construction of a more inclusive and empathetic society, where all identities are recognized and valued. Art, in its capacity to move and transform, thus becomes a powerful tool for social change, promoting greater understanding and acceptance of human diversity.
El presente proyecto de titulación llamado “Representación LGBTIQ+ mediante y a través del arte” tiene como finalidad la creación de una serie de retratos surrealistas que representen y den visibilidad a personas de la comunidad en Ecuador. Este trabajo busca informar y concienciar sobre las problemáticas de discriminación que aún enfrenta este colectivo minoritario. La discriminación y la invisibilidad son problemas persistentes para la comunidad LGBTIQ+ en Ecuador, y este proyecto se propone enfrentar estos desafíos a través de la poderosa herramienta del arte. La elección del surrealismo como movimiento artístico se debe a su método característico de expresión, que explora el subconsciente basándose en las teorías de Freud. Este enfoque permite la creación de obras más creativas y fuera de lo convencional. El surrealismo, con su capacidad para representar lo irracional y lo onírico, ofrece un marco adecuado para reflejar las complejidades y las experiencias únicas de las personas LGBTIQ+. Al utilizar este estilo, se puede ir más allá de la representación literal y adentrarse en las profundidades del subconsciente, donde se encuentran muchas de las luchas internas y los aspectos ocultos de la identidad de estas personas. Mediante una serie de entrevistas realizadas a 5 individuos relacionados con la temática del proyecto, se planea realizar una serie de retratos que cuenten la historia de la comunidad LGBTIQ+ desde sus inicios hasta la actualidad. Estas entrevistas son fundamentales para capturar las vivencias personales y las historias de lucha y resistencia de cada individuo se busca no solo documentar sus experiencias, sino también interpretar y traducir estas historias en elementos visuales que conformen los retratos. Las obras en cuestión serán expuestas en redes sociales como Instagram y Facebook, con la finalidad de generar un espacio de debate sobre cómo el arte tiene el poder de cambiar percepciones y construir puentes entre diferentes partes de la sociedad. Las redes sociales se eligen como plataforma de exposición debido a su capacidad para llegar a una amplia audiencia y fomentar la interacción. Al compartir estas obras en línea, se espera no solo visibilizar las historias de las personas LGBTIQ+, sino también provocar reflexiones y conversaciones sobre la igualdad y la justicia social. Este proyecto es un ejemplo de cómo se puede utilizar el arte para abogar por la igualdad y la justicia social. A través de la creación de estos retratos surrealistas, se busca no solo representar a las personas LGBTIQ+, sino también honrar sus historias y sus luchas. Al darles un espacio en el arte, se contribuye a la construcción de una sociedad más inclusiva y empática, donde todas las identidades sean reconocidas y valoradas. El arte, en su capacidad para conmover y transformar, se convierte así en una herramienta poderosa para el cambio social, promoviendo una mayor comprensión y aceptación de la diversidad humana.
Keywords: ARTE; LUCHA SOCIAL; LGBT; MOVIMIENTO SOCIAL; SURREALISMO; ECUADOR; QUEER; TRANS.